THE EFFECTIVENESS OF TEAM-BASED LEARNING ON STUDENTS CRITICAL THINKING SKILLS IN THE EFL CLASSROOM - Bahar, Ananda Pratiwi; Ummi Khaerati Syam; Ilmiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine how is the effectiveness of Team Based Learning on student critical thinking skills in Efl classroom. This research used quantitative design method with pre-experimental class. The population of this research was taken from the students at the twelve grade of SMA Muhammadiyah Limbung. This population consisted of 125 students in consisted fifth classes. The researcher used purposive sampling technique to choose one class that consisted 22 students as the sample. The result of the students critical thinking skill in mean score in the pre-test (40.68), meanwhile the result of the students critical thinking skill mean score in the post-test (70.05). It was significant different score. The significance score showed between pre-test and post-test (27.364) The table shows Sig. (2-tailed) is 000, which is less than 0.005. A considerable difference was seen between pupils' pre-test and post-test results. As a result, hypothesis Ho was rejected and H1 accepted. It may be said that use of Team-based learning was affective on student critical thinking skill at SMA Muhammadiyah Limbung.